Development of SSR Markers and Genetic Diversity in White Birch (Betula platyphylla). - Wei Hao; Shengji Wang; Huajing Liu; Boru Zhou; Xinwang Wang; Tingbo Jiang (PLoS ONE, 2015)
In order to study genetic diversity of white birch (Betula platyphylla), 544 primer pairs were designed based on the genome-wide Solexa sequences. Among them, 215 primer pairs showed polymorphism between five genotypes and 111 primer pairs that presented clear visible bands in genotyping 41 white birch plants that were collected from 6 different geographical regions. A total of 717 alleles were obtained at 111 loci with a range of 2 to 12 alleles per locus. The results of statistic analysis showed that polymorphic frequency of the alleles ranged from 17% to 100% with a mean of 55.85%; polymorphism information content (PIC) of the loci was from 0.09 to 0.58 with a mean of 0.30; and gene diversity between the tested genotypes was from 0.01 to 0.66 with a mean of 0.36. The results also indicated that major allele frequency ranged from 0.39 to 1.00 with an mean of 0.75; expected heterozygosity from 0.22 to 0.54 with a mean of 0.46; observed heterozygosity from 0.02 to 0.95 with a mean of 0.26; Nei's index from 0.21 to 0.54 with a mean of 0.46; and Shannon's Information from 0.26 to 0.87 with a mean of 0.66. The 41 white birch genotypes at the 111 selected SSR loci showed low to moderate similarity (0.025-0.610), indicating complicated genetic diversity among the white birch collections. The UPGMA-based clustering analysis of the allelic constitution of 41 white birch genotypes at 111 SSR loci suggested that the six different geographical regions can be further separated into four clusters at a similarity coefficient of 0.22. Genotypes from Huanren and Liangshui provenances were grouped into Cluster I, genotypes from Xiaobeihu and Qingyuan provenances into Cluster II, genotypes from Finland provenance into Cluster III, and genotypes from Maoershan into Cluster IV. The information provided in this study could help for genetic improvement and germplasm conservation, evaluation and utilization in white birch tree breeding program.